O professor de Português e o ensino de crianças e jovens refugiados - Sequeira, Rosa Maria; Cardoso, Sílvia Margarida Azevedo (Linguarum Arena, 2020)
This study aims to know the capability of Portuguese teachers to promote the inclusion of children and teenagers refugees when it comes to language teaching, in the context of reception measures. Data was collected on 32 Portuguese language teachers. We conclude that there are some problems with teamwork, that teachers feel the lack of flexibility to develop intercultural competence and few of them contacted with concepts as intercultural dialogue, or intercultural cultural consciousness, intercultural mediation and global citizenship. Teachers’ main preoccupations are the language of communication; planning adaptation; unfamiliarity with culture and syllabus of schools of the students; the possibility of cultural shock; integration difficulties; lack of attractive and suitable didactic resources and materials. We thus conclude that interculturality is seen as a problem and is perceived as being difficult to manage, with academic activities falling short of the desirable development of critical intercultural awareness.